WELL LOG APPLICATION TO DETERMINE DISPOSAL ZONE OF OIL PRODUCTION WASTE, MENGGALA FORMATION, GHAITSA FIELD, CENTRAL SUMATRA BASIN - Kenan Diponegoro (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2013)
PT. Chevron Pacific Indonesia (PT. CPI) is one of the main operators of exploration and exploitation of oil and gas in the Central Sumatera Basin, Riau Province. One of the production field is Ghaitsa Field. Petroleum exploitation activities carried liquid waste, which the government requires PT. CPI to manage the liquid waste so as not to pollute the environment through the Oil and Gas Law No. 22 of 2001. Therefore, PT. CPI took the solution to diposal or injection wells for wastewater treatment. Research is underway to find the location of disposal wells in Ghaitsa Field. Foramations that are the focus of research is Menggala Formation because it has met the basic requirements of disposal locations. These requirements are unproductive formation of oil and is the deepest formation.In completing this final project, the methodology is divided into two, namely the descriptive and analytical method, which consists of primary data and secondary data. The analytical method performed well log analysis is the qualitative and quantitative petrophysical and subsurface mapping with primary data used includes 16 well log data, while secondary data include 3D seismic data and velocity models.Menggala Formation is composed by Sandstone dominated and shale inserts, the depositional environment based on GRN log electrofacies analysis is cylindrical patterns are interpreted as part of a braided fluvial (Kendall, 2003). Geological structures such as faults inversion develops in the southern part of the N-S direction, normal faults and shear faults in the central and northern parts of the N-S direction, and the anticline and a syncline with a NW-SE direction. Petrophysical analysis generate values average porosity is 23%, the value of the permeability of about 322 mD to obtain the value of the capacity of the reservoir volume 263,614,635.47 barrels of water with the recommended disposal wells are wells IW 1 is located at coordinates x: 195 and y: 570 at a depth of -2000 feet to -2300 feet.